An optical contact force sensor for tactile sensing based on specklegram detection from concatenated multimode fibers. (November 2021) - Liu, Yan; Zou, Xiaoli; Qin, Qi; Li, Guangde; Tan, Zhongwei; Wang, Muguang; Yan, Fengping
Highlights: Specklegrams from different concatenated fibers are compared and analyzed. Sensor head with MMF housed in enables conversion of force into fiber deformation. Changes in the ZNCC of fiber specklegrams characterize the fiber deformation. Concatenated fiber enables good force sensing and is insensitive to disturbance. Specklegram detection from concatenated fiber applied to tactile sensing is shown. Abstract: An optical contact force sensor based on specklegram detection was proposed and validated for tactile sensing in this research. The specklegrams from different multimode fiber (MMF) based structures were firstly analyzed and compared in detail. Two of the structures based on the concatenation of MMF and few mode fiber (FMF) were selected. In the experiment, only the section of MMF is housed in a specially designed sensor head by 3D printing and the FMF section is used to lead the light out to the camera. The concatenated fiber structure enables the sensitive response to the applied force and shows insensitivity to the disturbance along the light lead-out part. With a contact force applying to the sensor head, bending of the MMF could be induced, which results in a deformed specklegram. In this way, the zero-mean normalized cross-correlation coefficient of the fiber specklegrams goes down with the increase of the contact force. For the selected fiber structure with different parameters, different sensitivity and different measurement ranges of force are realized, of which the largest linear measurement range of force is 0–23 N. Compared with only adopting MMF, the proposed scheme presents better stability together with a large measurement range and the flexibly adjusted sensitivity by changing the parameters of the fiber or the sensor head.